K+E = 66

K-6 = 2(E-6)= 2E -12

K+6 = 2E

K-66=-E

72 = 3E

E = 24 years old for Esmeralda

K = 66-24 = 42 years old for Keegan

24 and 42 years old

they sum to 66

6 years ago they wre 18 and 36. 36 = 2(18)

Bon F.

asked • 02/23/21The sum of the ages of Keegan and Esmeralda is 66 years. 6 years ago, Keegan's age was 2 times Esmeralda's age. How old is Keegan now?

Follow
•
1

Add comment

More

Report

K+E = 66

K-6 = 2(E-6)= 2E -12

K+6 = 2E

K-66=-E

72 = 3E

E = 24 years old for Esmeralda

K = 66-24 = 42 years old for Keegan

24 and 42 years old

they sum to 66

6 years ago they wre 18 and 36. 36 = 2(18)

You can use system of equations to solve this problem. If K is Keegan age and E is Esmeralda age then K+E=66. Six years ago Keegan was (K-6) and Esmeralda was (E-6) then we have (K-6)=2(E-6) .

Next, you combine these two equation into a system of equations and solve it to find Keegan and Esmeralda age. If solve correctly you should get K=42 and E=22

Ask a question for free

Get a free answer to a quick problem.

Most questions answered within 4 hours.

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.